Recovery of Motor Function Following Spinal Cord Injury 2016
DOI: 10.5772/63759
|View full text |Cite
|
Sign up to set email alerts
|

Normal Distribution and Plasticity of Serotonin Receptors after Spinal Cord Injury and Their Impacts on Motor Outputs

Abstract: Following spinal cord injury (SCI) a series of anatomical and functional plastic changes occur in the spinal cord, including reorganization of the spinal neuronal network, alteration of properties of interneurons and motoneurons as well as up-or down-regulation of different neurotransmitter receptors. In mammalian spinal cord, one of the important neurotransmitters, serotonin (5-HT), plays an essential role in modulating sensory, motor and autonomic functions. Following SCI, especially complete spinal cord les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 199 publications
(352 reference statements)
0
10
0
Order By: Relevance
“…5-HT 1A and 5-HT 2A receptors are distributed to the spinal cord and involved in cardiovascular performance. [10][11][12] In parallel, previous studies reported the presence of dopamine (DA) receptors in the spinal cord that participate in the regulation of multiple body functions. 13 Recent investigations revealed that specific interneurons are capable of synthesizing DA or have the potential to produce serotonin after an SCI interrupts descending neurotransmitter transport.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…5-HT 1A and 5-HT 2A receptors are distributed to the spinal cord and involved in cardiovascular performance. [10][11][12] In parallel, previous studies reported the presence of dopamine (DA) receptors in the spinal cord that participate in the regulation of multiple body functions. 13 Recent investigations revealed that specific interneurons are capable of synthesizing DA or have the potential to produce serotonin after an SCI interrupts descending neurotransmitter transport.…”
Section: Introductionmentioning
confidence: 88%
“…14,15 Albeit their spinal receptors may undergo plasticity to up/downregulate activity, it is evidenced that these neurotransmitter receptors remain present and functional in the spinal cord after injury regardless of the lack of supraspinal inputs. 10 Therefore, these spinal receptors could be a potential target for drug treatment to repair cardiovascular function. The purpose of this study was first to characterize cardiovascular consequences of a crushed rat SCI model, and then to define the effects of stimulating spinal serotonin or DA receptors on hemodynamic performance.…”
Section: Introductionmentioning
confidence: 99%
“…The drastic and sudden decrease in serotonin availability below the lesion renders spinal networks unexcitable and unresponsive [ 82 , 83 ], which critically contributes to SCI-induced paralysis [ 80 ]. The importance of 5-HT to movement is exemplified by the restoration of neuronal excitability and associated locomotor behaviors observed when 5-HT or 5-HT receptor agonists are administered, both in the acute or chronic phase of injury (reviewed in [ 84 ]). However, while spinal 5-HT availability is undeniably decreased after SCI, the serotonergic system remains challenging to study compared to other systems, as it comprises intraspinal and supraspinal neurons, as well as numerous receptors, all of which are highly plastic.…”
Section: Effect Of Rehabilitation On Spinal Network Below the Injurymentioning
confidence: 99%
“…We and others have previously argued that 5-HT 2A and 5-HT 7 receptors are important in the initiation and control of locomotion [ 3 12 ], and that these receptors mediate hindlimb locomotor recovery produced in paraplegic animals after replacement of 5-HT neurons into the sublesional spinal cord by grafts of fetal brainstem [ 10 , 13 ]. One of the effects of spinal cord transection, which interrupts the 5-HT pathway from the brainstem to the spinal cord, is plasticity in 5-HT receptors of spinal MNs [ 14 , 15 ]. The 5-HT 7 receptors have been implicated in control of MNs or reflexes involved in respiration, jaw movement, micturition, and locomotion [ 16 21 ] as well as in the control of pain after spinal cord injury [ 22 , 23 ], while the 5-HT 2A receptor has been implicated in the control of respiration, development of spasticity in tail and hindlimb digit MNs, and the recovery of locomotor capability after spinal cord injury [ 24 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, 5-HT 2A receptors are differentially distributed on MNs to the physiological extensor soleus muscle and extensor digitorum longus, a physiological flexor muscle [ 39 ]. Plasticity in the 5-HT 2A receptor protein has been examined after sacral spinal cord injury, where the changes have been suggested to underlie the development of tail spasticity (reviewed in [ 14 , 15 ]). Contusive spinal cord injury at the thoracic level resulted in upregulation of 5-HT 2A receptor protein in MNs of the rostral dorsolateral nucleus innervating the plantar muscles of the foot, with an associated increase in the H-reflex recorded from the plantar muscles of the hindpaw [ 40 ].…”
Section: Introductionmentioning
confidence: 99%